Advances of neuroimaging findings in medication overuse headache - Wang, Xiaoni; Zhang, Dan; Yang, Yi; Zheng, Jiaxin; Jiang, Mengze; Wang, Jin (Frontiers in Neuroscience, 2025)
Medication overuse headache (MOH) is a chronic secondary headache disorder that develops from excessive analgesic use. The prevalence of MOH is estimated 1–2% in the general population, reaching up to 50% among individuals with chronic headache. Although the pathophysiological mechanisms underlying MOH remain incompletely understood, neuroimaging studies have provided valuable insights into its developments. This review synthesizes current evidence demonstrating that MOH is associated with structural and functional alterations in two key neural systems: (1) the pain matrix involved in nociceptive processing, (2) the mesocorticolimbic reward circuitry implicated in addictive behaviors. Importantly, certain structural and functional changes show partial reversibility following medication withdrawal. Nevertheless, longitudinal studies with larger sample sizes are necessary to establish causal relationships between these neurobiological changes and the development/maintenance of MOH, which remains essential for developing targeted interventions.